2019
DOI: 10.20944/preprints201909.0214.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ERCP in Super-Aged Patients Considering Difficult Cannulation: Challenges and Adverse Events

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) is a routinely used therapeutic procedure for the biliary and pancreatic diseases. Population aging may increase the typical indications of ERCP and come with more complexity and difficulties, especially in cannulation. This study aimed to evaluate the incidence, causes, and management of difficult biliary cannulation during ERCP in super-aged patients and the role of difficult cannulation as a risk factor for adverse events. A total of 614 patients, underw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Most studies showed that the PEP rate of TPS is similar to other advanced cannulation methods; even NKP could be better to avoid PEP 18,20,21 . However, limited studies have prospectively compared PEP rate in TPS and NKP, in addition to lack of information on using uniform PEP preventive methods or pancreatic stent implantation in the TPS cases, which could make PEP rate in TPS even lower 5,18 .…”
Section: Discussionmentioning
confidence: 96%
“…Most studies showed that the PEP rate of TPS is similar to other advanced cannulation methods; even NKP could be better to avoid PEP 18,20,21 . However, limited studies have prospectively compared PEP rate in TPS and NKP, in addition to lack of information on using uniform PEP preventive methods or pancreatic stent implantation in the TPS cases, which could make PEP rate in TPS even lower 5,18 .…”
Section: Discussionmentioning
confidence: 96%